GSTM1 and GSTT1 Gene Polymorphisms with Gallbladder Carcinoma: GSTM1 and GSTT1 Gene Polymorphisms - Fang, Jianming; Fang, Fazhuang; Huang, Jianxin; Zhang, Xiaodong; Wang, Hongjuan (Cellular and Molecular Biology, 2022)
In order to explore the relationship between GSTM1 and GSTT1 gene polymorphisms and gallbladder cancer, so as to find a better treatment and prevention of gallbladder cancer and improve the treatment effect. In this paper, 247 patients with gallbladder cancer were selected for the experiment, including 187 male patients and 60 female patients. The total number of patients was randomly divided into two groups, namely the case group and the control group. The patients in normal condition and after treatment of tumor tissue and adjacent non-tumor tissue gene detection, and then through the logistic regression model to analyze the data. After the experiment, we found that the frequency ratio of GSTM1 and GSTT1 in gallbladder cancer patients before treatment was 57.33% and 52.37%, which was very high, which was very disadvantageous in gene detection. However, after treatment, the frequency of deletion of the two genes was 45.73% and 51.02%, which was significantly reduced. The reduced gene ratio is very beneficial to the observation of gallbladder cancer. Therefore, the surgical treatment of gallbladder cancer before the first drug after gene testing, in the understanding of various principles, will have twice the result with half the effort.